COVID-19-Induced Fatal Thrombotic Thrombocytopenic Purpura in a Healthy Young Patient - Mariana Codevila Buere Pereira; Bruna Ruschel; Bruna Schneider; Vitor Salomão Gonçalves Melo de Melgar; Tatiana Helena Rech (Case Reports in Critical Care)
Since the global coronavirus disease 2019 (COVID-19) pandemic began, findings indicate that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) might induce autoimmune disorders. Thrombotic thrombocytopenic purpura (TTP) is a devastating disease if not emergently treated. It presents with severe thrombocytopenia, microangiopathic hemolytic anemia, and neurologic findings with or without renal insufficiency. The antibody-mediated reduced activity of the disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) induces the accumulation of ultrahigh-molecular-weight multimers of von Willebrand factor, leading to platelet aggregation and thrombosis. TTP can be an unusual presentation of COVID-19 disease mediated by the virus-induced immune response. We report a case of a healthy young patient presenting with the classic TTP pentad a few days after a diagnosis of COVID-19 confirmed by a positive SARS-CoV-2 RT-PCR test. The patient was initially treated with high-dose methylprednisolone and fresh frozen plasma until she was transferred to a tertiary care facility and plasma exchange was available. She evolved with a malignant ischemic vascular accident and was declared brain-dead 24 hours after the first plasma exchange section.